Prevalence and intensity of parasitic worm eggs of bali cow (Bos sondaicus Muller) feces from two different shed sanitations - Hafidz Uddin Hidayat; Nurul Suwartiningsih (Universitas Ahmad Dahlan, 2022)
Bali cow (Bos sondaicus Muller) is a cow that is widely maintained. Poor sanitation of cowshed is caused by cow feces that are not cleaned, and become a medium of transmission of gastrointestinal worm parasites. The study aimed to compare the prevalence, intensity and degree of infection of parasitic worm eggs in the feces of Bali cows from two different shed sanitation, from a shed with poor sanitation and a from shed with good sanitation. The eggs of parasitic worms are separated from feces by buoyant methods and by sedimentation methods. The results showed that 15 out of 16 samples of Balinese cows contained parasites with a total of 43 worm eggs. The number of parasites obtained from Bali cow feces samples from shed with poor sanitation is higher (31 worm eggs) than that obtained from a well-sanitized shed (12 worm eggs). The prevalence, intensity and degree of parasitic infection obtained from Bali cow feces samples from a shed with poor sanitation were higher than those obtained from a shed with good sanitation. The results showed that poor shed sanitation increased the chances of cows being infected with parasites so that the prevalence, intensity and degree of infection of parasitic worm eggs were also high.